Fostering a Creativity Culture: how culture can foster creativity in design students across a semester - Springer,Leonardo (2022)
Abstract Design has evolved into a comprehensive discipline, its core areas (communication, product, spaces, web, service) are a fraction of its wide-ranging outcome which has expanded into specialized fields of knowledge. The creative process greatly depends on previously acquired cognitive knowledge (socio-cultural and moral values). This usually originates within a cultural context, that provides visual, audio, and kinaesthetic manifestations, requiring interpretations and understanding of both the designer and the end-user. Design education had to adapt and evolve accordingly, applying methodologies and encompassing a transdisciplinary approach involving research, art, materials, technology, processes, and human interactions in the development of design solutions, emphasizing understanding over output. Global culture and cultural expressions have created a need in design schools to foster understanding, encouraging students to ask questions and develop awareness of wide-ranging design manifestations, thus addressing a variety of subjects without prejudice of individual beliefs. This learning and sharing of experiences can produce meaningful results, considering that civilization is influenced by cultural interactions, regarding users and products/services. These are assessed as good/bad and beautiful/ugly, depending on specific cultural background and distinct interpretations. Cultural unawareness impairs individuals to develop creative thinking and accordingly innovative solutions. The issue presents itself, how to encourage creativity among design students, many unaware of their cultural background, thus overcoming the fear of failure, developing curiosity, applying research methodologies, and engaging in discussions that foster a mindfulness about design.